Political Communication Strategy of the Indonesian Labor Party in the Campaign for Labor Rights - Zainal Abidin; Shofiatul Husnah (PT ARRUS Intelektual Indonesia, 2023)
Within Indonesia's democratic framework, political parties ostensibly committed to public welfare face a pervasive skepticism rooted in the perceived prioritization of elite interests. This erosion of trust stems from instances of corruption, collusion, and nepotism. Addressing this, the previously dormant Labor Party underwent a revival, introducing new symbols and leadership. Employing a descriptive analytical approach through interviews, observation, and documentation, this research delves into the party's political communication strategies. Findings reveal the adoption of the AIDDA strategy (Attention, Interest, Desire, Decision, Action) as a persuasive tool aligning with the party's emphasis on social capital over financial resources. This strategic shift aims to rebuild public trust and underscores a commitment to the workforce's well-being. The party's nuanced approach to political communication emerges as a response to broader challenges, presenting a persuasive narrative to engage the community within the confines of Indonesia's intricate political landscape.